2018
DOI: 10.3389/fnbeh.2018.00170
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen-Rich Water Ameliorates Autistic-Like Behavioral Abnormalities in Valproic Acid-Treated Adolescent Mice Offspring

Abstract: Due to its anti-inflammatory and anti-oxidative effects, recent research has demonstrated that molecular hydrogen can serve as a new medical approach for depression, anxiety and traumatic brain injury. However, its potential effects on neurodevelopmental diseases, such as autism are still elusive. The present study aims to investigate the potential effects of hydrogen-rich water (HRW) administration on valproic acid (VPA)-induced autistic-like behavioral deficits, and the associated underlying mechanism in ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The effects of H 2 -rich water on antioxidant system have been tested largely within in vitro or animal models, with limited human data from few patient studies allowing substantiation of the beneficial roles of the water [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of H 2 -rich water on antioxidant system have been tested largely within in vitro or animal models, with limited human data from few patient studies allowing substantiation of the beneficial roles of the water [19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…The use of VPA during pregnancy significantly increases the risk of ASD in offspring (Nicolini & Fahnestock, 2018). In ASD treatment, research indicated that a ketogenic diet (Castro et al, 2017), astaxanthin (Al-Amin et al, 2015), zinc (Cezar et al, 2018), hydrogen-rich water (Guo et al, 2018), and agomelatine (Kumar, Sharma & Sharma, 2015) may improve behavioral disorder and oxidative stress in a prenatal VPA-induced mice model of autism. Molecular research should focus on solving this problems, both genetic/environmental interactions, and how they affect neurodevelopmental changes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, regular drinking of hydrogen water reduced motor impairment in patients with PD (97). A similar study using an autism spectrum disorder mouse model also reported amelioration of the autisticlike behavior in mice (98). However, the specific mechanism of hydrogen in modulating cognitive impairment is still unknown.…”
Section: Modifications Of Microbial Molecules In Parkinson's Diseasementioning
confidence: 91%